Fatal hyperpyrexia caused by xylazine: a case report - Dai, Ping; Chen, Yanqing; Luo, Xianqin; Zhou, Zhiqiang; Shi, Mengdi; Genjiafu, Aerbusili; Jian, Xiangdong (Frontiers in Pharmacology, 2024)
Xylazine is used in veterinary medicine as a sedative, analgesic, and muscle relaxant. However, in recent decades, it has frequently been detected in illicit drugs. Xylazine poisoning is characterized by depression of the central nervous and cardiovascular systems. Herein, we present a case of a 41-year-old man who not only had severe depression of the central nervous and cardiovascular systems, but also developed hyperpyrexia during the treatment of xylazine poisoning, which led to his death 3 days after poisoning. This case indicates that, in addition to its other effects, xylazine may also cause hyperthermia, which has not yet been reported in humans.